Optimization of tomato (Solanum lycopersicum L.) juice fermentation process and analysis of its metabolites during fermentation - Zhao, Lei; Maimaitiyiming, Ruxianguli; Hong, Jingyang; Wang, Liang; Mu, Ying; Liu, Bingze; Zhang, Huimin; Chen, Keping; Aihaiti, Aihemaitijiang (Frontiers in Nutrition, 2024)
In this study, the tomato juice was co-fermented with multistrains, optimized by uniform experimental design and response surface methodology. Superoxide dismutase activity reached 496.67 U/g and lycopene content reached 77.12μg/g when P. pentosaceus(53.79%), L. casei(13.17%), L. plantarum(19.87%), L. fermentum(13.17%). To gain insight into the dynamics of metabolites during the tomato fermentation juice process multivariate statistical analysis was performed using the UHPLC-QE-MS/MS method. The main metabolites are peptides, amino acids carbohydrates, organic acids ,and phospholipids. Carbohydrates were fully retained at the end of fermentation.The content of galactitol increased from the initial 5.389 to 6.607 while the content of cytarabine decreased by 29% and uridine by 44%. Meanwhile, phospholipids (PS, PE, PC, PG, PI) were all retained by more than 70%. Terpenoids (16-deacetylgairin, (+)-Royleanone, artemisinin) were increased to varying degrees, which gives them good nutritional value and biological activity. Organic acids (malic and citric) were reduced and lactic acid content was increased, changing its original flavor and making it more palatable to the general population. These results demonstrate the beneficial effects of Lactic acid bacteria fermentation on tomato juice and also provide a theoretical basis for the metabolic process of fermented tomato juice.